Efektivitas Pengelolaan Dana Desa ahun 2018 Bagi Pembangunan Infrastruktur di Desa Ngimbangan Kecamatan Mojosari, Kabupaten Mojokerto - Yudistira, Archan; Indartuti, Endang; Soenarjanto, Bagoes (Universitas 17 Agustus 1945 Surabaya, 2019)
Village funds are funds originating from the budget of state revenues and expenditures that are allocated for villages that are transferred through the district / city expenditure budget and are used to finance government administration, implementation of development, and community empowerment. Ngimbangan Village is a village located in Mojosari Subdistrict, Mojokerto Regency which carries out management of village funds for infrastructure development. This study aims to determine the effectiveness of village fund management for infrastructure development in the balance villages. Data and information are collected through observation, interviews, documentation, and literature. The analysis used in this study is descriptive analysis. The results of the study show that the management of village funds in the village of Ngimbangan in terms of the accuracy of carrying out orders (planning, implementation and reporting) led by the Village Head as the highest leader in the Village Government has been effective.Keywords: Village Fund Management, Accuracy in Making Orders, Effective